Avoidance of Total Knee Arthroplasty in Early Osteoarthritis of the Knee with Intra-Articular Implantation of Autologous Activated Peripheral Blood Stem Cells versus Hyaluronic Acid: A Randomized Controlled Trial with Differential Effects of Growth Factor Addition - Thana Turajane; Ukrit Chaveewanakorn; Warachaya Fongsarun; Jongjate Aojanepong; Konstantinos I. Papadopoulos (Hindawi Limited, 2017)
In this randomized controlled trial, in early osteoarthritis (OA) that failed conservative intervention, the need for total knee arthroplasty (TKA) and WOMAC scores were evaluated, following a combination of arthroscopic microdrilling mesenchymal cell stimulation (MCS) and repeated intra-articular (IA) autologous activated peripheral blood stem cells (AAPBSCs) with growth factor addition (GFA) and hyaluronic acid (HA) versus IA-HA alone. Leukapheresis-harvested AAPBSCs were administered as three weekly IA injections combined with HA and GFA (platelet-rich plasma [PRP] and granulocyte colony-stimulating factor [hG-CSF]) and MCS in group 1 and in group 2 but without hG-CSF while group 3 received IA-HA alone. Each group of 20 patients was evaluated at baseline and at 1, 6, and, 12 months. At 12 months, all patients in the AAPBSC groups were surgical intervention free compared to three patients needing TKA in group 3 (p<0.033). Total WOMAC scores showed statistically significant improvements at 6 and 12 months for the AAPBSC groups versus controls. There were no notable adverse events. We have shown avoidance of TKA in the AAPBSC groups at 12 months and potent, early, and sustained symptom alleviation through GFA versus HA alone. Differential effects of hG-CSF were noted with an earlier onset of symptom alleviation throughout.